Changes in muscle activities and kinematics due to simulated leg length inequalities - Siebers, Hannah Lena; Eschweiler, Joerg; Migliorini, Filippo; Quack, Valentin Michael; Tingart, Markus; Betsch, Marcel (Biomedizinische Technik, 2021)
Muscle imbalances are a leading cause of musculoskeletal problems. One example are leg length inequalities (LLIs). This study aimed to analyze the effect of different (simulated) LLIs on back and leg muscles in combination with kinematic compensation mechanics. Therefore, 20 healthy volunteers were analyzed during walking with artificial LLIs (0-4 cm). The effect of different amounts of LLIs and significant differences to the reference condition without LLI were calculated of maximal joint angles, mean muscle activity, and its symmetry index. While walking, LLIs led to higher muscle activity and asymmetry of back muscles, by increased lumbar lateral flexion and pelvic obliquity. The rectus femoris showed higher values, independent of the amount of LLI, whereas the activity of the gastrocnemius on the shorter leg increased. The hip and knee flexion of the long leg increased significantly with increasing LLIs, like the knee extension and the ankle plantarflexion of the shorter leg. The described compensation mechanisms are explained by a dynamic lengthening of the short and shortening of the longer leg, which is associated with increased and asymmetrical muscle activity. Presenting this overview is important for a better understanding of the effects of LLIs to improve diagnostic and therapy in the future.
CRIS-Team Scopus Importer:2022-07-20
Keywords: EMG; gait analysis; leg length differences